PRINSIP-PRINSIP HIDUP MASYARAKAT MADURA SEPERTI TERKISAH DALAM CERITA RAKYATNYA - Azhar, Iqbal Nurul; Sari H, Erika Citra (Balai Bahasa Jawa Timur, 2017)
The purpose of this study is to explain the Madurese principles towards life using folktales perspectives. The focus of this study is to describe how Madurese principles are reflected in Ma-durese folktales. The data of this study were 32 legends obtained from informants living in several regencies in Madura. The method used to collect the data was interview. The method used to analyze the data was the Miles and Huberman?s interactive data analysis model. From the data analysis, it has been found that the 32 legends contain 10 Madurese principals which have not been revealed before. The principles are: the appreciation towards water, the appreciation towards trees, the protection of self-esteem, the ownership of the provision of life, the respect for women, the precaution attitude, the belief in the purification of the inner self, the belief in the importance of religious knowledge, and the respect for kiai.